PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP STRESS KERJA DAN KEPUASAN KERJA PERAWAT DI RUMAH SAKIT IBU DAN ANAK ERIA BUNDA PEKANBARU - Obed, Sihotang Ryan; Sri, Indarti; Ahmad, Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aimed to determine the effect of workload and compensation on job stress and job satisfaction of nurses at Eria Bunda Mother and Child Hospital Pekanbaru. The population of this study included 104 nurses who worked at the Eria Bunda Mother and Child Hospital Pekanbaru. Primary data were collected by using a questionnaire as an instrument to prove the results of the study. This study used the loading factor and boots rapping with the PLS (Partial Least Square) method for the hypothesis. The sampling technique was saturated sampling method (104 nurses at Eria Bunda Mother and Child Hospital Pekanbaru). The results showed that: 1) there was a positive and significant effect of workload on work stress at Eria Bunda Pekanbaru Mother and Child Hospital nurses, 2) there was a negative and significant effect of compensation on work stress on nurses at Eria Bunda Mother and Child Hospital Pekanbaru, 3) there was a negative and significant effect of job satisfaction on the workload of nurses at Eria Bunda Mother and Child Hospital Pekanbaru, 4) there was a positive and significant effect of compensation on job satisfaction of nurses at Eria Bunda Mother and Child Hospital Pekanbaru, 5) there was a negative influence and significant job stress on job satisfaction of nurses at Eria Bunda Pekanbaru Mother and Child Hospital, 6) there was a negative and significant influence on workload on nurse job satisfaction through job stress at Eria Bunda Pekanbaru Mother and Child Hospital, 7) there was a positive and significant compensation effect on satisfaction the work of the nurses through job stress at the Eria Bunda Mother and Hospital Pekanbaru.Keywords: Workload, Compensation, Work Stress, Job Satisfaction